Teacher Professional Learning in International Education Practice and Perspectives from the Vocational Education and Training Sector - Tran, Ly Thi (Springer International Publishing, 2018)
This book examines the impact of internationalization, student mobility and transnational workforce mobility on the changing nature of teacher work and teacher professional learning in the Vocational Education and Training (VET) sector. Derived from a three-year project funded by the Australian Research Council across more than 30 VET and HE institutions, this is the first book that explores teacher professional learning in international education. The authors address how teachers position their professional responsibilities and learning in relation to the institutional structure, internationalization agenda and policy fields in which their profession is embedded by drawing on both empirical evidence and key concepts and models of teacher professional learning. This pioneering text provides international education and VET policy makers, practitioners, educators and researchers with unique insights and practical implications for enhancing teacher professional learning and capabilities in international education. Ly Tran is an Associate Professor and Australian Research Council Future Fellow at Deakin University, Australia. As a recognized scholar in the field of international education, she has published widely on the subject and has won numerous fellowships, prizes and awards for her research, including the International Education Association of Australia Excellence Award for her book on teaching international students in VET. She is lead author of 'Higher education in Vietnam: Flexibility, mobility and practicality in the global knowledge economy', published by Palgrave Macmillan. Truc Le is a Research Fellow at Deakin University, Australia. Her research interests include transnational academic mobility, faculty development, and curriculum and pedagogy. She is a co-author of the book entitled 'Higher education in Vietnam: Flexibility, mobility and practicality in the global knowledge economy' published by Palgrave Macmillan.